ANALYSIS OF FACTORS INFLUENCING READINESS FOR ELECTRONIC MEDICAL RECORDS IMPLEMENTATION IN HOSPITALS: LITERATURE REVIEW - Nyoman Tri Maryanthi; I Nyoman Gede Bayu Wiratama Suwedia; Nitya Jyoti (Bajang Institute, 2026)
Abstract: Background: Digital transformation in the healthcare sector thru the implementation of Electronic Medical Records (EMR) plays a crucial role in improving service quality and operational efficiency. However, its implementation still faces various obstacles in several developing countries, including Indonesia, such as low adoption rates and high system failures. This indicates that implementation readiness, including aspects of human resources, technology, organization, and regulation, is a key factor in the successful application of EHR. Objective: This study aims to analyze and identify the factors influencing the readiness for EHR implementation in hospitals thru a literature review of various studies. Method: This research employs a systematic narrative review design without meta-analysis to identify and synthesize the factors affecting the readiness for electronic health record implementation in hospitals. Literature search was conducted thru Google Scholar and PubMed for the years 2016–2026 using a combination of keywords and the Boolean operator AND. Inclusion criteria included full-text articles in Indonesian or English that were relevant to the topic and derived from scientific publications. The selection process used the PRISMA flow and yielded 10 articles that met the research criteria. Results: The research findings indicate that the readiness for RME implementation in hospitals is influenced by various factors, namely human resources (HR), technological infrastructure, organizational and managerial factors, as well as policy, regulation, and funding aspects. Conclusion: The readiness for RME implementation in hospitals is influenced by multidimensional factors: human resources, technological infrastructure, organizational-managerial aspects, and policy and funding. Improvement in readiness is carried out thru HR training, infrastructure strengthening, thorough planning, and the formulation of clear SOPs.